Pneumoperitônio com dióxido de carbono associado a três posições para laparoscopia - Leme, Marshal Costa (2001)
The present study evaluated the changes in abdominal insufflation with carbon dioxide, with constant pressure of 15mmHg. In this experiment 12 dogs, adults mongrel were used. After having installed the pneumoperitonium, the animals were positioned in Trendelenburg, reversed Trendelenburg and horizontal position. In each one of the mentioned positions, the dogs stayed for a period of 30 minutes, for evaluation of alterations in the variables of saturation of oxygen in the hemoglobin, heart rate, breathing rate, arterial blood pressure, pH, partial pressure of CO2 and partial pressure of O2. There was no influences of the positioning on the studied variables. The heart rate, breathing rate, pH and the partial pressure of CO2 had significant difference when compared at the time controls.